Investigation of the pharmacological effect and mechanism of mountain-cultivated ginseng and garden ginseng in cardiovascular diseases based on network pharmacology and zebrafish experiments - Yu, Ting; Zhang, Yan-Xin; Liu, Xin-Juan; Chen, Dan-Qing; Wang, Dan-Dan; Zhu, Guo-Qin; Gao, Qi (Frontiers in Pharmacology, 2022)
The secondary metabolites of Mountain-cultivated ginseng (MCG) and Garden ginseng (GG) vary greatly due to their different growth environments. Thus far, their differences in pharmacological effects on cardiovascular disease (CVD) and clinical application remain unclear. We used UPLC-Q-TOF/MS to distinguish MCG and GG, PLS-DA and OPLS-DA models were used to analyze the relationship between metabolite expression and sample categories. Network pharmacology-based approach was developed to reveal the active mechanism of differential metabolite on CVD. We applied the research on the role of MCG and GG in angiogenesis and protection of damaged blood vessels in the vascular injury model of zebrafish. 11 differential metabolites between MCG and GG were screened out by UPLC-Q-TOF /MS conditions. In addition, 149 common targets genes of metabolites and CVD were obtained, these activities were related to the TP53, SRC, UBA52, RPS27A, UBB, STAT3, IDH1, VEGFA, GSK3B, F2 and adjust the PI3K-Akt signaling pathway, TNF signaling pathway, HIF-1 signaling pathway to the curative effect of treating CVD. Both Ginseng can promote sub-intestinal vessel plexus growth and protect injured intersegmental vessels through HIF-1α/VEGF signaling pathway and dose-dependent manner. Additionally, MCG has a stronger impact than GG. This is the first time to combine metabolomics and network pharmacology to study the difference between MCG and GG on CVD, which provided some theoretical basis for the clinical treatment of CVD with two kinds of Ginsengs.